(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
Addressing scientific disinformation has been a major concern worldwide. Recognizing the intersubjective processes of relationships of trust established in the midst of disputes over scientific information, this article presents the results of an exploratory study with young high schoolers from public schools in the state of Rio de Janeiro, seeking to understand their media consumption habits on science and how they establish trust about the actors that produce scientific information. The findings of this research point out that young people value individual freedom values, for relations of recognition of scientific and professorial authority – only if they are dialogical –, distrustful about the media and search for greater participation when social conflicts stem from non-recognition